Preparation and characterization of immobilized indole−3−butyric acid on silver−cerium oxide nanoparticles for improving its stability and utilization in the study of plant root formation indices - Ghorbani, Masoumeh; Kahrizi, Danial; Arkan, Elham; Yu, Zhennan (Frontiers in Plant Science, 2025)
IntroductionIn recent years, nanocarriers have emerged as sophisticated platforms for the encapsulation and targeted delivery of agricultural chemicals, with particular emphasis on auxins. Owing to their remarkable potential to enhance bioavailability and optimize crop productivity, these nanotechnological systems have garnered considerable scientific interest. MethodsHere, the synthesis and efficacy of silver-cerium oxide (ceria) nanoparticles (Ag@CeO2 NPs) as a metal-oxide nanocarrier for loading the hormone indole-3-butyric acid (IBA) and its effect on tobacco plant rooting were investigated. Tobacco plant stems were cultured in different concentrations of IBA−Ag@CeO2 NPs (1, 2, and 3 mgL-1) in plant culture medium, and rooting indices were evaluated after 4 weeks. Results and DiscussionThe mean particle size (MPS) of IBAloaded Ag@CeO₂ nanoparticles was determined to be 389 nm via dynamic light scattering (DLS) analysis. Scanning electron microscopy (SEM) further revealed that the nanoparticles possessed a predominantly spherical morphology, with a mean diameter of approximately 136 nm. The successful immobilization of IBA onto the Ag@CeO₂ nanocarriers was confirmed by Fourier-transform infrared spectroscopy (FTIR), which identified the characteristic absorption peaks of the hormone on the nanoparticle surface. Moreover, the IBA loading process achieved a hormone loading efficiency (HLE) of 45% and an encapsulation efficiency (EE) of approximately 90%. The results showed that IBA−Ag@CeO2 NPs at a concentration of 2 mgL-1 had the highest efficiency in promoting the rooting of tobacco (Nicotiana tabacum) plants compared with other treatments. Our results suggest that Ag@CeO2 NPs function as an effective nanocarrier for delivering the IBA hormone, highlighting their potential applications in agricultural practices.